PENERAPAN MUHASABAH DIRI UNTUK MENINGKATKAN KUALITAS AKHLAK MAHASANTRI PUTRI IDIA PRENDUAN - Muru’atul Afifah; Irma Nur’Aini (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
Self-muhasabah is one of the methods of moral education that is put forward by the teachers at IDIA Prenduan. Various forms of programs are structured to direct the students to always reflect on themselves, such as spiritual cleansing activities every dawn on Fridays (Kulsub) and mandatory activities for the management of the minister for studies and da'wah or (Menkada) Ma'had Student Executive Board (BEMA) at IDIA Prenduan and other things. In this study, the focus of the research was how to apply self-reflection to improve the moral quality of female female students of IDIA Prenduan and what are the supporting and inhibiting factors in the application of self-muhasabah to improve the moral quality of female female students of IDIA Prenduan. And the purpose of this study is to describe the application of self-muhasabah in improving the moral quality of female female students of IDIA Prenduan. This study uses a qualitative descriptive method of phenomelogy. Data collection techniques include interviews, observation and documentation. The data analysis techniques include data collection, data reduction, data presentation and verification. The results of this study are the application of self-muhasabah to improve moral quality in the form of dawn lectures, istirham, morning lectures, tahajjud prayers, it can be seen that this application can improve the quality of mahasantri morals such as self-muhasabah activities. The supporting factors of this activity are Kyai and Nyai who have qualified knowledge and discipline of the mahasantri while the obstacle is the lack of enthusiasm from the mahasatri in self-contemplation which is held at dawn, due to the dense activities carried out. So that some students feel sleepy and this is a form of lack of faith in Allah SWT.